Ag@MOF-199 metal organic framework for selective detection of nickel ions in aqueous media. Issue 4 (15th February 2023) - Bodkhe, Gajanan A.; Khandagale, Dhanashri D.; More, Mayuri S.; Deshmukh, Megha A.; Ingle, Nikesh N.; Sayyad, Pasha W.; Mahadik, Manasi M.; Shirsat, Sumedh M.; Al-Buriahi, M.S.; Tsai, Meng-Lin; Kim, Myunghee; Shirsat, Mahendra D.
Abstract: Monitoring heavy metal ions (HMIs) in water is always a challenging and vital issue due to their hazardous effects on the environment and human health. Therefore, it is necessary to detect heavy metals in the water. Herein, we first-time report the use of silver nanoparticles (Ag NPs) incorporated copper benzene carboxylate (MOF-199) metal organic framework (Ag@MOF-199) for detection of heavy metal ions in water. A glassy carbon electrode-modified Ag@MOF-199 electrochemical sensor probe was fabricated and showed a selective and sensitive response towards nickel (Ni(II)) ions only by cyclic voltammetry. The Ag@MOF-199-based sensor did not offer any cyclic voltammetric sensing response towards cadmium (Cd(II)), lead (Pb(III)), chromium (Cr(III)), and ferric (Fe(III)) ions (1 μM/L) at pH values ranging from 3 to 10. The Ag@MOF-199 sensor displayed high sensitivity of 1.48 μA/nM on the exponential scale for Ni(II) ions at pH 7 and a lower detection limit of 6.06 nM/L with good reproducibility below US EPA suggested maximum contamination limit. The synthesized Ag@MOF-199 was characterized by spectroscopic (viz. UV–visible spectroscopy, Raman spectroscopy and mapping, energy dispersive spectroscopy (EDS), Fourier transform infrared (FTIR) spectroscopy), surface area (viz. Brunauer–Emmett-Teller surface area analysis), electrochemical activity (viz. cyclic voltammetry, electrochemical impedance spectroscopy), morphological (viz. field emission scanning electron microscopy (FE-SEM)), structural (viz. X-ray diffraction (XRD)), and thermogravimetric analysis.